2004
DOI: 10.1242/jcs.01361
|View full text |Cite
|
Sign up to set email alerts
|

A hypophosphorylated form of RPA34 is a specific component of pre-replication centers

Abstract: IntroductionReplication protein A (RPA) is a stable complex of three different subunits (p70, p34 and p11) that participates in different cellular processes: DNA replication, recombination and repair (Wold, 1997). The RPA70 subunit has a high affinity for single-stranded DNA, but a DNA-binding activity that is associated with the RPA34 and RPA11 subunits (Bochkareva et al., 1998). Cell-cycle-regulated phosphorylation of RPA34 at the G1-S transition has been described (Din et al., 1990;Fang and Newport, 1993;Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 89 publications
(125 reference statements)
6
26
0
Order By: Relevance
“…However this differs from mammalian cells where no RPA foci are observed in normal G1 cells (Dimitrova et al, 1999;Dimitrova and Gilbert, 2000a;2000b), but mainly in S-phase cells (Dimitrova et al, 1999). It has been speculated that the RPA foci observed in Xenopus are unrelated to DNA replication and represent non-specific storage of RPA prior to its requirement in replication (Francon et al, 2004).…”
Section: The Role Of Ssbs In Dna Replicationmentioning
confidence: 74%
See 1 more Smart Citation
“…However this differs from mammalian cells where no RPA foci are observed in normal G1 cells (Dimitrova et al, 1999;Dimitrova and Gilbert, 2000a;2000b), but mainly in S-phase cells (Dimitrova et al, 1999). It has been speculated that the RPA foci observed in Xenopus are unrelated to DNA replication and represent non-specific storage of RPA prior to its requirement in replication (Francon et al, 2004).…”
Section: The Role Of Ssbs In Dna Replicationmentioning
confidence: 74%
“…The switch from hyper to hypo-phosphorylated RPA is likely to be catalysed by the 1A/2A phosphatases, as treatment with okadaic acid inhibits the dephosphorylation of RPA34 (Francon et al, 2004). This is further supported by the inhibition of DNA replication in Xenopus egg extracts immuno-depleted of phosphatase 2A (Lin et al, 1998).…”
Section: The Role Of Ssbs In Dna Replicationmentioning
confidence: 94%
“…RPA, replication factor C (RFC), PCNA, minichromosome maintenance proteins, and DNA polymerase ␦ have been previously shown to be required for AAV replication in vitro and in cells (54,55,58). Interestingly, RPA phosphorylation excludes it from cellular sites of replication (25,82) and may alter its DNA affinity in order to promote repair (23). We have also previously shown that Rep can bind RPA (76) although we do not know how this interaction may be affected by phosphorylation.…”
Section: Discussionmentioning
confidence: 92%
“…However, in our study, we found that inhibition of RPA32 phosphorylation by silencing ATR did not affect MVC DNA replication. In fact, it has been reported that RPA32 phosphorylation appears to occur outside the cellular replication sites (33,84). CGK733 inhibits both ATM and ATR activation (1,10,25,35,89,92) and was the most effective inhibitor of DDR-mediated cell death and cell cycle arrest in MVC-infected cells.…”
Section: Discussionmentioning
confidence: 99%